Industrial electronics - Gnanavadivel, J (Anuradha Publications, 2011)
The main aim of this book is to provide a basic concepts of power semiconductor devices, phase controlled converters, DC choppers, inverters, DC drives, AC drives, control circuits and industrial applications in alucid way with neat sketches and waveforms. Each chapter contains short question and answers to get complete knowledge of the subject. Large number of worked examples are added to the clarity of the subject matter.